Pengaruh Kualitas Produk, Kepercayaan Merek, dan Komunikasi dari Mulut Ke Mulut terhadap Keputusan Pembelian Produk Skincare Korea Pada Konsumen di Banjarmasin - Herliani; Maryono; Noor Hidayanti (Business Administration, FISIP ULM, 2022)
ABSTRACT : This study aims to determine and examine the significant effect of Partial and Simultaneous Product Quality, Brand Trust and Word of Mouth Communication on Korean Skincare Product Purchase Decisions on consumers in Banjarmasin. The approach in this study uses a quantitative approach. The population and sample are Korean skincare product consumers in Banjarmasin with a total sample of 140 respondents, using purposive sampling technique. The technique of collecting data is a questionnaire, the technique of analyzing the data is using Multiple Linear Regression Analysis with SPSS 25.0. The results of this study prove that the quality of the product partially significant effect on purchasing decisions with a large influence of 0.442 or (44.2%) positive and significant effect on purchasing decisions. Brand Trust has a positive and significant effect on Purchase Decisions with a large influence of 0.338 or 33.8%. Word of mouth does not have a significant effect partially on purchasing decisions with a large effect of 0.017 or 1.7%. Simultaneous test on the magnitude of the effect is 54.4% while 45.6% is the influence of other variables not examined in this study Keywords: Product Quality, Brand Trust, Word Of Mouth Communication, Purchase Decision